PENGARUH KINERJA KEUANGAN PEMERINTAH PUSAT TERHADAP AKUNTABILITAS PELAPORAN KEUANGAN - Fitri, Meliyana; Khotimah, Husnul (KEUNIS, 2022)
The purpose of this study was to examine the effect of the central government's financial performance on financial reporting accountability. The data sample taken is the financial statements of the Ministry of the Republic of Indonesia totalling 125 data through the purposive sampling method for the 2015-2019 period. The type of data used is secondary data. Financial performance is proxied by solvency, revenue effectiveness and expenditure efficiency, while financial reporting accountability is proxied by BPK RI audit opinion. The results showed that solvency did not contribute to increasing financial reporting accountability, while income effectiveness and spending efficiency were able to increase financial reporting accountability.